ANALISIS EFEKTIVITAS APLIKASI SISTEM KEUANGAN DESA DALAM MENINGKATKAN AKUNTANBILITAS PENGELOLAAN ALOKASI DANA DESA DI TANJUNG MERAHE KECAMATAN SELESAI KABUPATEN LANGKAT - Devi Natalia; Yenni Samri Juliati Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of conducting this research is to find out how the implementation and effectiveness of the siskeudes application is in increasing accountability in managing village fund allocation in Tanjung Merahe Village, Finish District, Langkat Regency. The research uses qualitative methods with a descriptive approach. Data sources are obtained from primary data and secondary data. The data collection techniques used were observation, interviews and documentation. Data analysis techniques include data reduction stages, data presentation and drawing conclusions. The results of the research show that the Tanjung Merahe Village Government has used the siskeudes application in managing the allocation of village funds very well, seen from the implementation level of 77% which was obtained using the statistical analysis formula according to Dean J Champion and also the village financial system application is said to be effective because it has succeeded in fulfilling indicators of the effectiveness of the information system initiated by Delon Mclean as well as accountability reports on village fund allocations produced in accordance with established regulations, also supported by the implementation of village fund allocation budget realization with a percentage level of 100% as measured by the effectiveness ratio.